Circulatory Dynamics During Pulmonary Vein Isolation Using the Second‐Generation Cryoballoon. Issue 10 (10th October 2017) - Kajiyama, Takatsugu; Miyazaki, Shinsuke; Watanabe, Tomonori; Yamao, Kazuya; Kusa, Shigeki; Igarashi, Miyako; Nakamura, Hiroaki; Hachiya, Hitoshi; Iesaka, Yoshito
Abstract : Background: Circulatory dynamics change during pulmonary vein (PV) isolation using cryoballoons. This study sought to investigate the circulatory dynamics during cryoballoon‐based PV isolation procedures and the contributing factors. Methods and Results: This study retrospectively included 35 atrial fibrillation patients who underwent PV isolation with 28‐mm second‐generation cryoballoons and single 3‐minute freeze techniques. Blood pressures were continuously monitored via arterial lines. The left ventricular function was evaluated with intracardiac echocardiography throughout the procedure in 5 additional patients. Overall, 126 cryoapplications without interrupting freezing were analyzed. Systolic blood pressure (SBP) significantly increased during freezing (138.7±28.0 to 148.0±27.2 mm Hg, P <0.001) and sharply dropped (136.3±26.0 to 95.0±17.9 mm Hg, P <0.001) during a mean of 21.0±8.0 seconds after releasing the occlusion during thawing. In the multivariate analyses, the left PVs ( P =0.008) and lower baseline SBP ( P <0.001) correlated with a larger SBP rise, whereas a higher baseline SBP ( P <0.001), left PVs ( P =0.017), lower balloon nadir temperature ( P =0.027), and female sex ( P =0.045) correlated with larger SBP drops. These changes were similarly observed regardless of preprocedural atropine administration and the target PV order. PV occlusions without freezing exhibited no SBP change. PV antrum freezing without occlusions similarly increased the SBP, but the SBP drop was significantly smaller than that with occlusions ( P <0.001). The SBP drop time‐course paralleled the left ventricular ejection fraction increase (66.8±8.1% to 79.3±6.7%, P <0.001) and systemic vascular resistance index decrease (2667±1024 to 1937±513 dynes‐sec/cm 2 per m 2, P =0.002). Conclusions: With second‐generation cryoballoon‐based PV isolation, SBP significantly increased during freezing owing to atrial tissue freezing and dropped sharply after releasing the occlusion, presumably because of the peripheral vascular resistance decrease mainly by circulating chilled blood.